2007
DOI: 10.1029/2006tc002030
|View full text |Cite
|
Sign up to set email alerts
|

Strain and rotation rate from GPS in Tibet, Anatolia, and the Altiplano

Abstract: [1] Deformation measured by regional GPS networks in continental plateaus reflects the geologic and tectonic variability of the plateaus. For two collisional plateaus (Tibet and Anatolia) and one noncollisional (the Altiplano), we analyze the regional strain and rotation rate by inverting GPS velocities to calculate the full two-dimensional velocity gradient tensor. To test the method, we use gridded velocities determined from an elastic block model for the eastern Mediterranean/ Middle East region and show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
120
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 74 publications
13
120
0
3
Order By: Relevance
“…They suggested that the strain rate fields determined by geodetic measurements taken on a decadal timescale are consistent with geological observations on a 10 4 years timescale. Allmendinger et al [66] derived 2-D strain and rotation rate fields from a GPS velocity field using both the nearest neighbor and distance weighted approach. Their results showed that the principal infinitesimal strain rate axes in Tibet are consistent with large, long term geological structures similar to England and Molnar [2].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the strain rate fields determined by geodetic measurements taken on a decadal timescale are consistent with geological observations on a 10 4 years timescale. Allmendinger et al [66] derived 2-D strain and rotation rate fields from a GPS velocity field using both the nearest neighbor and distance weighted approach. Their results showed that the principal infinitesimal strain rate axes in Tibet are consistent with large, long term geological structures similar to England and Molnar [2].…”
Section: Discussionmentioning
confidence: 99%
“…We calculated a smooth and continuous strain rate field for the Tibetan Plateau and surroundings from combined GPS data, which is similar to results of Allmendinger et al [2007], England and Molnar [2005], and Gan et al [2007], by employing an updated code for interpolation of strain rate [Shen et al, 2015]. At a given site, the horizontal velocity field in its vicinity was approximated by a bilinear function and represented by translation, rotation, and strain rates.…”
Section: 1002/2015gl064347mentioning
confidence: 99%
“…where indexes i and j correspond to spatial coordinates, t i is the velocity with respect to the grid point, e ij is the velocity gradient tensor, u i is the individual GPS velocities, and Dx j is the baseline between each station and the grid point (Shen et al 1996;Allmendinger et al 2007;Crowell et al 2013). The following inverse problem is set up to solve for the velocity gradient tensor ¼ Gl …”
Section: Strain Rate Computationmentioning
confidence: 99%